Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui Model Pembelajaran Berbasis Masalah (PBL) pada Materi Kemampuanku dan Keterbatasanku di Kelas VII SMP Assisi Kota Batak - Hermawaty Nadeak; Yohanes Umbu Lede; Paulus Asriadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the improvement of learning outcomes of Catholic Religious Education and Character Education for students of class VII-1 at SMP Assisi Kota Batak through the use of the problem-based learning (PBL) model. This type of research is classroom action research (Classroom Action Research) which is carried out collaboratively between researchers and teachers. In the material My abilities and limitations, the problem based learning (PBL) learning model is one of the learning models where students are trained to think critically to find solutions to the problems given. The study was conducted in two cycles, each cycle consisting of four components, namely planning, action, observation and reflection. Data collection techniques used in this study were interviews, observations, documentation and tests. Data analysis was carried out in 3 stages, namely reduction, data presentation and drawing conclusions. The results obtained in this study: cycle 1 was carried out for 2 meetings with the percentage of students whose scores were above the KKM of 42.85%. Cycle 2 was carried out for 2 meetings with the percentage of students whose scores were above the KKM of 92.85%. Based on the research results, it was found that the problem-based learning (PBL) learning model can improve the learning outcomes of class VII-1 students at SMP Assisi Kota Batak.